Pengaruh Metode Ceramah Terhadap Keterampilan Menyimak pada Pembelajaran Bahasa Indonesia Siswa Kelas X Merdeka A SMA Negeri 14 Jeneponto - Alfiah Megawati; Sitti Rabiah; Ihramsari Akidah (Jayapangus Press, 2023)
This study aims to determine the effect of the Lecture Method on Listening Skills in Indonesian Language Learning for Class X Merdeka A Students of SMA Negeri 14 Jeneponto. The research was conducted at SMAN 14 Jeneponto in the even semester of 2022/2023 academic year. This research is a type of experimental research and data were analyzed using SPSS version 25.0. The population of this study were students of class X consisting of 3 classes. The sample of this research was class X Merdeka A, totaling 32 students who were divided into two groups, 16 students as the experimental group and 16 students as the control group. The sample was selected by simple random sampling technique. This type of research is quasi-experimental with a pretest posttest control group design. The data obtained were analyzed descriptively and inferentially. In this study, the experimental group and control group tested the hypothesis of learning outcomes using paired sample test analysis because the data were normally distributed and homogeneous. The hypothesis was tested with the SPSS version 25.0 for windows program using paired sample test analysis with testing: accept H0 if the significance obtained is greater than >0.05 and H0 is rejected if the significance obtained is less than <0.05. The results of this study can be known based on hypothesis testing, where the two groups show that the sig. is 0.000 <0.05 means that H0 is rejected and H1 is accepted, which means that there is an influence of the lecture method on listening skills. Therefore, the conclusion of this study is that there is an effect of using the lecture method on students' listening skills.